Implementing Patient-Initiated Follow-Up (PIFU) Into a Psychiatric Outpatient Setting - Thomas Scurr; Elizabeth Frayne; Isabelle Needham (BJPsych Open)
Aims: The cost to the NHS of missed appointments each year is highly significant. PIFU is an alternative to the conventional follow-up model where patients request appointments as-needed in attempt to reduce this cost, and is part of the Outpatient Recovery and Transformation Programme component of the NHS Long-Term Plan. This model is well established in chronic conditions under secondary care like gynaecology and rheumatology outpatients but has more recently been brought into psychiatry. Currently, there is minimal research on the suitability of this model in psychiatry. The Exmouth CMHT in Devon have had a PIFU model for the last 4 years, and this project evaluated this model and analysed the associated costs.